A comparative study on the flexural strengths of composites used as direct core buildup materials - Fernandez, Femalyn L.
Badly broken down coronal portions of the teeth may still be restorable using direct core build up materials which must possess properties able to resist the strong masticatory forces in addition to be able to retain the final coronal restoration. One of the important mechanical properties is the material's flexural strength which is a combination of its compressive, tensile and shear strength. This study aims to determine if there is a significant difference among the flexural strength of composite marketed as direct core buildup materials (CBCo), and Light cured nanocomposites (LCCo), as direct core buildup materials. One CBCo (Rebilda) and Two LCCo (Grandio and Filtek z350) were evaluated. 10 specimens of each composite materials were prepared in a stainless steel mould with dimensions of 25mm x 2mm x 2mm. They were then subjected to a 3 point bending test with the use of a Universal Testing Machine with a crosshead speed of 0.75mm/min. Results of the study show that there is no statistically significant difference in the flexural strengths of the conventionally light cured nanocomposites and composites marketed as direct core build-ups.